Improving scientific rigour in conservation evaluations and a plea deal for transparency on potential biases. Issue 5 (28th May 2020) - Josefsson, Jonas; Hiron, Matthew; Arlt, Debora; Auffret, Alistair G.; Berg, Åke; Chevalier, Mathieu; Glimskär, Anders; Hartman, Göran; Kačergytė, Ineta; Klein, Julian; Knape, Jonas; Laugen, Ane T.; et al.
Abstract: The delivery of rigorous and unbiased evidence on the effects of interventions lay at the heart of the scientific method. Here we examine scientific papers evaluating agri‐environment schemes, the principal instrument to mitigate farmland biodiversity declines worldwide. Despite previous warnings about rudimentary study designs in this field, we found that the majority of studies published between 2008 and 2017 still lack robust study designs to strictly evaluate intervention effects. Potential sources of bias that arise from the correlative nature are rarely mentioned, and results are still promoted by using a causal language. This lack of robust study designs likely results from poor integration of research and policy, while the erroneous use of causal language and an unwillingness to discuss bias may stem from publication pressures. We conclude that scientific reporting and discussion of study limitations in intervention research must improve and propose some practices toward this goal.